Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/jso.23604
|View full text |Cite
|
Sign up to set email alerts
|

Age and molecular subtypes: Impact on surgical decisions

Abstract: Both young patient age and breast cancer molecular subtype impact local recurrence rates and long-term prognosis for women with breast cancer. Although rates of local recurrence are consistently higher in young women and those with high-risk molecular subtypes, this risk does not appear to be overcome by more extensive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…On the other hand, the association of age with HER2 overexpression was evident among both groups in this study and most significant in the British series (p<0.0001). That was illustrated by a sharp rise in the rate of that biomarker in younger women under 50 years; thus supporting prior studies which documented that young patients frequently present with HER2 overexpression when compared to their older counterparts [45]. A recent survey showed that HER2 positive frequencies increased when the patients were diagnosed at yes stages, with larger tumors, poorly differentiated grades, estrogen receptor-negative disease and younger ages (46).…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, the association of age with HER2 overexpression was evident among both groups in this study and most significant in the British series (p<0.0001). That was illustrated by a sharp rise in the rate of that biomarker in younger women under 50 years; thus supporting prior studies which documented that young patients frequently present with HER2 overexpression when compared to their older counterparts [45]. A recent survey showed that HER2 positive frequencies increased when the patients were diagnosed at yes stages, with larger tumors, poorly differentiated grades, estrogen receptor-negative disease and younger ages (46).…”
Section: Discussionsupporting
confidence: 80%
“…Young age at diagnosis is also associated with an unfavorable prognosis 8 . Data assessing differences in age-dependent prognosis in TNBC patients are limited and have yielded conflicting results 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“… 13 Although randomized controlled trials (RCTs) suggest equivalent survival for mastectomy and BCS, very few young patients were included in these analyses. 6 , 14 Indeed, young women are not routinely analyzed or reported separately in individual RCTs of BCS versus mastectomy, and any that do have very few women ≤40 years presented. 12 …”
mentioning
confidence: 99%